2002
DOI: 10.1097/00061198-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy in Primary Congenital Glaucoma With Megalocornea

Abstract: Confocal microscopy is a diagnostic tool used to evaluate microscopic aspects of Haab striae and endothelial morphologic changes in glaucomatous megalocornea. Unsuspected alterations, such as nerves abnormalities and focal endothelial tractions by scar tissue, were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
4
25
2
1
Order By: Relevance
“…11,21 In accord with earlier studies 7,8 we found abnormalities in the Descemet's membrane and the endothelium in buphthalmic eyes. The density of endothelial cells was significantly lower in buphthalmic eyes, and the mean area of these cells was significantly larger compared with healthy eyes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…11,21 In accord with earlier studies 7,8 we found abnormalities in the Descemet's membrane and the endothelium in buphthalmic eyes. The density of endothelial cells was significantly lower in buphthalmic eyes, and the mean area of these cells was significantly larger compared with healthy eyes.…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not prove increased polymegathism and pleomorphism of the endothelial cells in buphthalmic eyes compared with the healthy eyes. The mean endothelial cell area in the buphthalmic eyes was smaller than that in the cases by Mastropasqua et al 8 Morphologic changes in the buphthalmic corneas were also clearly visible as Haab's striae on the Descemet's membranes. Very hyperreflective acellular scar tissue was also often observed at this tissue level.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…was clearly visualized with evident thin and reflective nerve fibers and without abnormal branching. 7 However, the small number of patients did not allow a quantitive analysis of the nerve plexus morphology. In our study, we investigated the morphology of corneal subbasal nerve plexus in young patients with PCG and demonstrated that both the nerve density (2108 ± 692 mm) and the total number of nerve fibers (12.3 ± 4.2) are significantly decreased.…”
mentioning
confidence: 99%